Improving the Energy-Based Dpa/Dema Attack Flow Preprocessing Performance - Lellis, Rodrigo; Soares, Rafael (Anais da Escola Regional de Alto Desempenho da Região Sul (ERAD-RS), 2021)
This paper proposes an improvement in the DPA/DEMA energy-based attack ﬂow to reduce the time to guess a secret cryptographic key from supposed secure systems. This was done through the recoding for C ++ language and parallelization of the algorithms. The results highlight a reduction of up to 78.53% in the execution time of preprocessing algorithms guaranteeing a good performance even in the majority of off-the-shelf processors available in the market.